"CloStyler" – mobile application to calculate the parameters of clothing blocks. Issue 1 (January 2021) - Zakharkevich, Oksana; Poluchovich, Iryna; Kuleshova, Svetlana; Koshevko, Juliya; Shvets, Galyna; Shvets, Alexander
Abstract: Due to the COVID19 pandemic that challenged our society with necessity of distance learning it is right to provide educational institutions with tools those would be accessible anytime and anyplace for students. The aim of the current research is to develop an app that will support students studying apparel design as well as their teachers. The prototyping method was used to explore aspects of an intended design of the app. The method of semantic differential was used in order to evaluate the prototype. Comparative analysis of the already existing apps and the developed one was used to determine the level of the app competitiveness. The mobile app "CloStyler" was developed by using MIT App Inventor. Using the app allows achieving the labor productivity growth up to 568.5 %. The reduction of time costs is 29.4-85.0 %. By means of the comparative analysis of the apps those are already on the market and the developed app "CloStylef" it was determined that "CloStyler" is better suited and better equipped for the task of computing the parameters of the basic blocks of clothing.